Deux gestes pour une grande danse - Jean-Michel Beaudet (Ateliers d'Anthropologie)
This brief article presents two gestures—one a woman’s, the other a man’s—linked to a major danced ceremony among the Wayãpi of the upper Oyapock. First we see that certain gestures can be sexed: just as the “sexual distribution” of tasks is very pronounced, the sexual distribution of gestures is quite perceptible here, and is learned early. But above all, I will attempt to detail the plastic aspects of these gestures, showing the distinctions and intersections between ordinary gesture and formal gesture within a single event, the whole ceremony.